Electromagnetic wave absorbing film and method for repairing the same
Patent Information
- Application Number
- CN202611486127.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-27
AI Technical Summary
一旦薄膜结构的完整性被破坏,电磁波吸收能力将会失效,传统解决方案如采用整体更换或局部修复方法,往往存在成本高昂、效率低下,难以满足快速修复的问题
[0047]本发明电磁波吸收薄膜材料中的碳基吸波填料通过由多聚甲醛溶于水转化成的甲醛与三聚氰胺聚合,将冷冻干燥后获得的三聚氰胺甲醛树脂粉末与碳纤维混合,通过高温热解将有机组分转换为碳骨架制备而成,通过优化短切碳纤维的加入量、热解温度及碳化时间,获得了具有优良性能的碳基吸波填料。使用该碳基吸波填料制备本发明电磁波吸收薄膜时,在维持电磁波吸收性能的同时可降低吸波填料的加入量,以保障电磁波吸收薄膜仍具有良好的可修复性能。
Smart Images

Figure CN122978636A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electromagnetic wave absorbing materials technology, and particularly relates to an electromagnetic wave absorbing thin film and its repair method. Background Technology
[0002] Electromagnetic wave absorbing materials play a crucial role in suppressing electromagnetic interference, improving the compatibility of electronic devices, ensuring information security, achieving target stealth, and constructing precise testing environments. Thin film materials, due to their advantages such as thinness, light weight, good flexibility, ease of integration, and excellent conformal bonding capabilities, have broad application prospects in the field of electromagnetic wave absorption.
[0003] Existing electromagnetic wave absorbing films suffer from inherent vulnerability and limited lifespan, severely restricting their reliability and application value during actual service. Once the integrity of the film structure is compromised, its electromagnetic wave absorption capability will fail. Traditional solutions, such as overall replacement or partial repair, are often costly, inefficient, and unable to meet the requirements for rapid repair.
[0004] For example, CN 112234364 A discloses a lightweight, flexible, multi-band electromagnetic wave absorbing material based on subwavelength materials and its preparation method. This method prepares an integrated flexible multi-band electromagnetic wave absorbing material, but the repair cost is high and it is difficult to replace quickly, affecting the long-term use of the system. CN 116376268 A discloses a method for preparing a self-healing electromagnetic composite material, but its resin-based repair technology is limited by the excessively long repair time and difficulty in dealing with large-area damage.
[0005] In summary, the following technical challenges still need to be overcome in the practical application of repairable electromagnetic wave absorbing films: First, the film substrate has poor compatibility, failing to meet the film formation requirements of various electromagnetic wave absorbing materials. Second, resin-based electromagnetic wave absorbing films have long repair times, making rapid repair difficult, and their repair capability for large-area damage is weak. Third, the mechanical properties of the repaired area are insufficient; current repair films are prone to fatigue cracking after repeated damage-repair cycles, affecting structural stability and the consistency of absorption performance. Therefore, it is necessary to research and develop an electromagnetic wave absorbing film that combines excellent electromagnetic wave absorption performance with rapid repairability. Summary of the Invention
[0006] To address the problems existing in the prior art, this invention proposes an electromagnetic wave absorbing thin film and a method for repairing it.
[0007] The technical solution of the present invention is as follows:
[0008] An electromagnetic wave absorbing film is obtained by uniformly dispersing the aforementioned carbon-based microwave absorbing filler in a thermoplastic elastomer solution to obtain a suspension, then coating the suspension onto the surface of an object to form a coating or film, and drying it. The thermoplastic elastomer solution is prepared by heating and dissolving the thermoplastic elastomer in an organic solvent. The amount of thermoplastic elastomer added is 1.8-2.2 times the total amount of paraformaldehyde, melamine, and chopped carbon fibers. The thermoplastic elastomer is a polyurethane-based thermoplastic elastomer, a styrene-based thermoplastic elastomer, or a thermoplastic styrene-butadiene rubber polymer. The organic solvent is selected from dimethylformamide, cyclohexane, or acetone. The carbon-based microwave absorbing filler is prepared by the following method:
[0009] Step 1: Mix paraformaldehyde and deionized water at a mass ratio of 1:5 to 1:10, and stir continuously at 80℃ to 100℃ for 1 to 2 hours to obtain a paraformaldehyde dispersion.
[0010] Step 2: Add melamine to the paraformaldehyde dispersion from Step 1, and continue stirring at 80℃~100℃ until the melamine is completely dissolved; wherein, the mass ratio of paraformaldehyde to melamine is 5:1~3:1;
[0011] Step 3: Add ammonia water dropwise to the paraformaldehyde dispersion in Step 2 containing melamine. The solution gradually changes from turbid to transparent to obtain a prepolymerized solution.
[0012] Step 4: After cooling the prepolymer solution obtained in Step 3 to room temperature, freeze-dry it for 2-3 days to obtain a white, fluffy melamine-formaldehyde resin powder.
[0013] Step 5: Take the melamine-formaldehyde resin powder and chopped carbon fibers from Step 4, mix them, add deionized water and stir evenly, then dry at 50-60°C to obtain a solid mixture; wherein, the amount of chopped carbon fibers added accounts for 5%-25% of the total mass of paraformaldehyde and melamine, and the amount of deionized water added accounts for 40%-60% of the total mass of paraformaldehyde, melamine and chopped carbon fibers.
[0014] Step 6: Pyrolyze the solid mixture from Step 5 in an inert gas for 300 to 360 minutes to prepare an aerogel, with the pyrolysis temperature controlled at 600 to 800°C.
[0015] Step 7: Grind the aerogel prepared in step 6 to obtain the carbon-based microwave absorbing filler of the present invention.
[0016] The carbon-based microwave absorbing filler used in this invention is prepared by polymerizing formaldehyde monomers (formaldehyde converted from paraformaldehyde dissolved in water) with melamine, freeze-drying them, mixing them with carbon fibers, and then converting them into a carbon skeleton through pyrolysis. It has good dielectric properties. When preparing electromagnetic wave absorbing films, the amount of microwave absorbing filler added can be reduced while maintaining electromagnetic wave absorption performance, so as to achieve good repairability.
[0017] Meanwhile, this invention uses thermoplastic elastomer mixed with carbon-based microwave absorbing filler to prepare an electromagnetic wave absorbing film. The carbon-based microwave absorbing filler can ensure the electromagnetic wave absorption performance of the film with a small amount of addition. Therefore, the amount of thermoplastic elastomer added is relatively high. In subsequent film repair, organic solvents can be used to induce the thermoplastic elastomer to swell, causing the molecular chains of the film material to rearrange and promoting the mutual diffusion and entanglement of molecular chains at the fracture interface, thereby achieving rapid repair.
[0018] Furthermore, in step 1, stirring is continued at a speed of 500–700 rpm. The stirring time and temperature should be adjusted to ensure that paraformaldehyde is fully dispersed to obtain an opaque dispersion.
[0019] In step 3, ammonia is added slowly, with the dropping rate controlled at 1 to 2 drops per second.
[0020] When adding ammonia in step 3, maintain the original temperature.
[0021] The stirring process after adding the chopped carbon fibers in step 5 can be carried out at room temperature. After stirring evenly, it can be directly dried at 50-60°C. The amount of deionized water added should be sufficient to effectively mix the melamine-formaldehyde resin powder and the chopped carbon fibers, preferably accounting for 50% of the total mass of paraformaldehyde, melamine, and chopped carbon fibers.
[0022] In step 6, the addition of an inert gas is sufficient to prevent the products from disappearing due to the reaction of organic matter and oxygen to produce carbon dioxide. Nitrogen (N2) is preferred.
[0023] This invention improves product performance by optimizing process parameters, and ultimately identifies the key parameters for promoting polymerization reaction—the ratio and temperature of paraformaldehyde and melamine, the key parameter for controlling the dielectric properties of carbon-based microwave absorbing filler—the amount of carbon fiber added, and the key parameters for ensuring sufficient carbonization of the carbon skeleton—the pyrolysis temperature and time.
[0024] The heating temperature used in step 1 can be selected according to the concentration of paraformaldehyde in deionized water. A lower temperature is used when the concentration is low, and a higher temperature is used when the concentration is high.
[0025] Furthermore, as a preferred embodiment, the mass ratio of paraformaldehyde to melamine is 3.9:1; and the amount of chopped carbon fiber added is 10% of the total mass of paraformaldehyde and melamine.
[0026] When the proportion of paraformaldehyde is too high, the polymerization will result in smaller molecular chains as the main component, preventing the formation of polymers with longer molecular chains. Simultaneously, maintaining the heating temperature in step 2 ensures the polymerization reaction proceeds. After freeze-drying, mixing with carbon fibers controls the pyrolysis behavior, achieving carbon skeletons of different sizes and regulating electromagnetic wave absorption to achieve optimal performance.
[0027] Furthermore, as a preferred embodiment, the pyrolysis temperature in step 6 is 700℃ and the pyrolysis time is 300 minutes.
[0028] Studies have found that excessively high pyrolysis temperatures can lead to excessively strong dielectric properties, resulting in a lack of electromagnetic wave absorption capabilities, while lower temperatures make it difficult for the polymer to transform into a carbon skeleton. This invention obtains a carbon-based microwave absorbing filler with optimal performance by controlling the amount of short-cut carbon fibers added, the pyrolysis temperature, and the sufficient carbonization time.
[0029] Furthermore, preferably, the thickness of the electromagnetic wave absorbing film is 1.5 mm to 3.0 mm.
[0030] More specifically, the above-mentioned electromagnetic wave absorbing thin film is prepared by the following steps:
[0031] Step 1: Dissolve the thermoplastic elastomer in an organic solvent and heat at 80℃~150℃ for 0.5h~4h to obtain a thermoplastic elastomer solution; the concentration of thermoplastic elastomer in the thermoplastic elastomer solution is 10 mg / mL~100 mg / mL.
[0032] Step 2: Add the above-mentioned carbon-based microwave absorbing filler to the thermoplastic elastomer solution, and disperse the carbon-based microwave absorbing filler evenly in the thermoplastic elastomer solution by mechanical stirring or ultrasonic dispersion to form a stable suspension;
[0033] Step 3: Apply the stable suspension to the surface of the object to form a coating or a thin film, and obtain an electromagnetic wave absorbing film after drying.
[0034] In step 2, when mechanical stirring is used to disperse the carbon-based microwave absorbing filler, the stirring speed is controlled at 300~1200 rpm and the stirring time is 1h~6h; when ultrasonic dispersion is used, the ultrasonic output power is 300 W and the ultrasonic time is 1h~4h.
[0035] In step 3, the drying temperature is 20℃~60℃ and the drying time is 12h~24h.
[0036] When a coating is formed on the surface of an object in step 3, the dip coating method can be used, with 1 to 10 dip coatings; a thin film can be formed separately by solution casting, and then dried at room temperature under windless conditions.
[0037] This invention also provides a rapid repair method for the above-mentioned electromagnetic wave absorbing thin film, comprising the following steps:
[0038] Step 1: When the electromagnetic wave absorbing film is damaged, remove surface contaminants by washing with water and then dry with hot air.
[0039] Step 2: Apply an organic solvent to the damaged area of the electromagnetic wave absorbing film or soak it in an organic solvent to induce swelling in the damaged area of the substrate; the organic solvent is selected from the organic solvent used in the preparation of the electromagnetic wave absorbing film.
[0040] Step 3: Join the swollen areas together and apply pressure to promote bonding of the swollen areas;
[0041] Step 4: After the solvent in the swollen area has completely evaporated, remove the pressure and stretch the repaired damaged area. If there is no breakage, the repair is complete.
[0042] Furthermore, in step 2 above, when applying organic solvent to the damaged area, the number of applications is 3 to 10, with an interval of 10 to 30 seconds between each application; when immersing the damaged area in organic solvent, the immersion time is 30 to 300 seconds.
[0043] In step 3, the splicing and bonding adopts either an overlapping method or a butt joint method, wherein the overlap width is 5mm~10mm; the applied pressure is 10~50N, and the pressure application time is 30~300 seconds.
[0044] This invention achieves simultaneous optimization of the dielectric properties of carbon-based microwave absorbing filler and the impedance matching of the thin film by synergistically controlling the amount of short-cut carbon fiber added (preferably 10%), the pyrolysis temperature (preferably 700℃), and the ratio of thermoplastic elastomer to carbon-based microwave absorbing filler (preferably 2:1), so that the electromagnetic wave absorbing film has excellent dielectric loss performance in the range of 2 to 18 GHz. Its absorption mechanism lies in the fact that the interconnected pores and continuous skeleton in the porous carbon skeleton are ground to form a large number of irregularly shaped polygonal carbon particles. These particles have sharp edges and rich angularity, which construct a continuous conductive network and rich heterogeneous interfaces in the thermoplastic elastomer matrix. On the one hand, the incident electromagnetic wave energy is dissipated as heat energy through conductive loss and interface polarization loss. On the other hand, the electromagnetic wave is significantly prolonged through multiple reflections and scattering paths between particles, thus achieving strong absorption at thin thicknesses. At the same time, the high proportion of thermoplastic elastomer (2:1 mass ratio with filler) keeps the dielectric constant of the film in a suitable range, which is conducive to impedance matching and promotes the entry of electromagnetic waves into the interior of the film, laying the foundation for strong absorption. The absorption peak is adjustable with thickness: it has an effective absorption bandwidth at different thicknesses, and the bandwidth does not change much. The absorption intensity also changes little with thickness, ultimately achieving a balance of advantages of "thin thickness, strong absorption, and wide frequency band".
[0045] This invention uses thermoplastic elastomers as the film matrix, whose molecular chains exhibit a linear or weakly cross-linked structure and good swelling response in organic solvents. During repair, the organic solvent used to prepare the film is coated or immersed in the damaged area. Solvent molecules rapidly penetrate the matrix and induce swelling of the molecular chains in the damaged area. The mobility of the swollen polymer chain segments is significantly enhanced, and under pressure, they diffuse across the fracture interface and re-entangle. After the solvent completely evaporates, the entangled molecular chains solidify and form a continuous and tight interfacial bond, thereby achieving rapid repair of the broken film. Compared with traditional thermosetting resin matrices, thermoplastic elastomers do not have the constraints of a three-dimensional cross-linked network. The solvent-induced healing process does not require high-temperature hot pressing or specialized equipment and can be completed within minutes (within 300 seconds) at room temperature, and can be repeated. After repair, the interfacial bond is tight, the mechanical properties are significantly restored, and the original flexibility and electromagnetic wave absorption properties of the film are maintained.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] The carbon-based microwave absorbing filler in the electromagnetic wave absorbing thin film material of this invention is prepared by polymerizing formaldehyde (formaldehyde converted from paraformaldehyde dissolved in water) with melamine, then mixing the freeze-dried melamine-formaldehyde resin powder with carbon fibers, and finally converting the organic components into a carbon skeleton through high-temperature pyrolysis. By optimizing the amount of short-cut carbon fibers added, the pyrolysis temperature, and the carbonization time, a carbon-based microwave absorbing filler with excellent performance was obtained. When using this carbon-based microwave absorbing filler to prepare the electromagnetic wave absorbing thin film of this invention, the amount of microwave absorbing filler added can be reduced while maintaining the electromagnetic wave absorption performance, so as to ensure that the electromagnetic wave absorbing thin film still has good repairability.
[0048] The electromagnetic wave absorbing thin film material of the present invention is prepared using the aforementioned carbon-based absorbing filler. In the 2–18 GHz range, although changes in film thickness affect the position of the absorption peak, the change in absorption peak intensity is small, and the effective absorption bandwidth does not change significantly. Therefore, this film exhibits an effective absorption bandwidth at different thicknesses, and even at low thicknesses, it combines the advantages of strong absorption and a wide frequency band, providing an electromagnetic wave absorbing material with good engineering application value.
[0049] The electromagnetic wave absorbing thin film material of the present invention also achieves synchronous optimization of the dielectric properties of the carbon-based absorbing filler and the impedance matching of the thin film by synergistically controlling the amount of short-cut carbon fiber added, the pyrolysis temperature, and the ratio of thermoplastic elastomer to carbon-based absorbing filler. This enables the electromagnetic wave absorbing thin film to have excellent dielectric loss performance in the range of 2 to 18 GHz, thereby increasing the applicability of the material.
[0050] The electromagnetic wave absorbing thin film material of the present invention reduces the proportion of microwave absorbing filler (i.e., the carbon-based microwave absorbing filler prepared by the present invention) during the preparation process. As a result, when repairing the film damage in the subsequent process, the swelling properties of the thermoplastic elastomer can be better utilized, and rapid repair within 300 seconds can be achieved, thus achieving excellent repair performance.
[0051] The present invention provides a rapid repair method for electromagnetic wave absorbing films. The repair process requires no high-temperature hot pressing or specialized equipment, is simple to operate, and has high repair efficiency. The same organic solvent used in the preparation of the electromagnetic wave absorbing film is employed during repair, making the repair operation convenient and fast. The selected solvent is highly volatile and requires only a small amount, effectively avoiding damage to the film substrate. After repair, the interface bonding is tight, mechanical properties are significantly restored, and the original flexibility and electromagnetic properties are maintained.
[0052] This invention uses thermoplastic elastomers as the film matrix, whose molecular chains have a linear or weakly cross-linked structure and exhibit good swelling response in organic solvents. During repair, the organic solvent used to prepare the film is coated or soaked in the damaged area. The solvent molecules quickly penetrate into the matrix and induce the molecular chains in the damaged area to swell, causing the fracture interface to diffuse and re-entangle, forming a continuous and tight interfacial bond, thereby achieving rapid repair of the fractured film.
[0053] The electromagnetic wave absorbing thin film and its rapid repair method of the present invention are particularly suitable for fields with high requirements for structural integrity, such as flexible electronic devices and wearable devices, and have broad application prospects. Attached Figure Description
[0054] Figure 1 This is a SEM image of the carbon-based microwave absorbing filler prepared in Example 1 of the present invention;
[0055] Figure 2 The electromagnetic wave absorption performance curves of the electromagnetic wave absorbing thin film prepared in Example 1 of this invention at different thicknesses are shown.
[0056] Figure 3 The electromagnetic wave absorption performance curves of the electromagnetic wave absorbing thin film at different thicknesses prepared in Example 2 of the present invention are shown.
[0057] Figure 4 The electromagnetic wave absorption performance curves of the electromagnetic wave absorbing thin film prepared in Comparative Example 1 of this invention are shown below for different thicknesses.
[0058] Figure 5 The electromagnetic wave absorption performance curves of the electromagnetic wave absorbing thin film at different thicknesses prepared in Example 3 of this invention are shown.
[0059] Figure 6 The electromagnetic wave absorption performance curves of the electromagnetic wave absorbing thin film at different thicknesses prepared in Example 4 of this invention are shown.
[0060] Figure 7 The electromagnetic wave absorption performance curves of the electromagnetic wave absorbing thin film with different thicknesses prepared in Example 5 of the present invention are shown.
[0061] Figure 8 The electromagnetic wave absorption performance curves of the electromagnetic wave absorbing thin film at different thicknesses prepared in Example 6 of this invention are shown.
[0062] Figure 9 The electromagnetic wave absorption performance curves of the electromagnetic wave absorbing thin film at different thicknesses prepared in Example 7 of this invention are shown.
[0063] Figure 10 This is a schematic diagram of the electromagnetic wave absorbing film repaired using the overlapping method in Embodiment 8 of the present invention;
[0064] Figure 11 This is a schematic diagram of the electromagnetic wave absorbing film repaired by the docking method in Embodiment 8 of the present invention;
[0065] Figure 12 This is a scanning electron microscope image of the electromagnetic wave absorbing film after repair in Embodiment 8 of the present invention; in the figure, A is the first film, B is the second film, and C is the repaired surface after swelling;
[0066] Figure 13 This is a comparison diagram of the mechanical properties of the electromagnetic wave absorbing film before and after repair in Embodiment 8 of the present invention; in the figure, a is before repair and b is after repair.
[0067] Figure 14 The electromagnetic wave absorption performance curves of the electromagnetic wave absorbing thin film prepared in Comparative Example 2 of this invention are shown below for different thicknesses.
[0068] Figure 15 The electromagnetic wave absorption performance curves of the electromagnetic wave absorbing thin film prepared in Comparative Example 3 of this invention are shown for different thicknesses. Detailed Implementation
[0069] The present invention will be further illustrated below with reference to the accompanying drawings and specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. After reading this invention, any modifications of the invention in various equivalent forms by those skilled in the art will fall within the scope defined by the appended claims.
[0070] The following are some of the raw materials used in the following examples:
[0071] The short-cut carbon fiber was purchased from Zhejiang Yamei Nanotechnology Co., Ltd., with the specific specifications being item number AM-C-068-2, particle size of 20-50nm, length of 10-20μm, and purity of 99.9%.
[0072] The carbonyl iron powder was purchased from Shanghai Macklin Biochemical Technology Co., Ltd. (MACKLIN), with the specific specification being item number C913576 and CAS number 7439-89-6.
[0073] The carbon nanotubes were purchased from Suzhou CarbonFeng Graphene Technology Co., Ltd., with the specific specifications being model CNTs-014C, carboxyl content of 0.51wt%, purity >95wt%, and length of 10-20μm.
[0074] Example 1
[0075] The electromagnetic wave absorbing thin film of the present invention is prepared by the following method:
[0076] Step 1: Add 19.5g of paraformaldehyde and 100g of deionized water to a beaker and heat to 90°C while stirring continuously.
[0077] Step 2: Add 5g of melamine to the solution and continue stirring at 90℃ until completely dissolved.
[0078] Step 3: Slowly add ammonia water dropwise until the solution changes from cloudy to transparent to obtain a prepolymerized solution.
[0079] Step 4: Cool the solution to room temperature and freeze-dry for 2 days to obtain a white, fluffy melamine-formaldehyde resin powder.
[0080] Step 5: Mix white fluffy melamine-formaldehyde resin powder with 2.45g of chopped carbon fiber (i.e., the chopped carbon fiber accounts for 10% of the total amount of paraformaldehyde and melamine added), and add 13.5mL of deionized water. Continue stirring until evenly dispersed, and then dry at 50℃ to obtain a solid mixture.
[0081] Step 6: Pyrolyze the solid mixture in an inert gas N2 for 300 minutes at a pyrolysis temperature of 700℃.
[0082] Step 7: After pyrolysis, the aerogel is ground to obtain carbon-based microwave absorbing filler.
[0083] Step 8: Dissolve styrene-butadiene-styrene in 1080 mL of cyclohexane at twice the total mass of the raw materials (paraformaldehyde + melamine + chopped carbon fibers) (approximately 54 g), and heat at 80 °C for 1 h to obtain a thermoplastic elastomer solution.
[0084] Step 9: Add the carbon-based microwave absorbing filler prepared in step 7 to the thermoplastic elastomer solution, and disperse the filler evenly in the thermoplastic elastomer solution by ultrasonic dispersion to form a stable suspension.
[0085] Step 10: Pour the stable suspension into a mold and form a thin film separately using the solution casting method. After drying, an electromagnetic wave absorbing film with rapid repair capability is obtained.
[0086] like Figure 1 The image shows the carbon-based microwave absorbing filler obtained in step 7. As can be seen from the figure, due to the introduction of carbon fibers, the microstructure of the material after pyrolysis consists of a large number of interconnected pores and a continuous skeleton. This loose and porous morphology endows the material with low density and abundant interfaces. After grinding, the original porous skeleton is broken down and transformed into a large number of irregularly shaped polygonal carbon particles. These polygonal particles have sharp edges and abundant angularity, which can significantly increase the paths of multiple reflections and scatterings when electromagnetic waves are incident, thereby greatly enhancing the reflection loss effect.
[0087] like Figure 2 As shown, this sample achieves the strongest reflection loss of −35.4dB at a thickness of 2.0mm, and can break through −20dB in the 7–17GHz range with thicknesses ranging from 1.5 to 3.0mm. Its advantage lies in achieving strong absorption with a thin thickness and tunable coverage of the entire C / X / Ku band through thickness adjustment. In terms of bandwidth, the optimal bandwidth is 4.1GHz, and it can cover a bandwidth of 6.4–18.0GHz with a low thickness.
[0088] Example 2
[0089] This embodiment uses the method of Example 1 to prepare the electromagnetic wave absorbing film, the difference being that the amount of short-cut carbon fiber added in step 5 is 4.9g.
[0090] like Figure 3 As shown, compared with Example 1, the electromagnetic wave absorbing film prepared in Example 2 exhibits a significant decline in overall absorption performance: within the main working thickness range (2.0–3.0 mm), the strongest reflection loss decreases from -35.4 dB to the order of -26.0 dB, and the effective absorption bandwidth of -10 dB also narrows from a maximum of 4.1 GHz to 3.7 GHz, with the continuous coverage range shrinking from 6.4–18.0 GHz to 7.0–18.0 GHz. Although a sharp peak of -54.8 dB still appears at 1.5 mm, this response is concentrated around 17.8 GHz with a bandwidth of only 2.9 GHz, which is closer to narrowband resonance than broadband strong absorption and cannot represent the overall performance. In summary, the broadband absorption capability, low-frequency coverage, and thickness robustness of Example 2 are all lower than those of Example 1, showing a trend of "narrow peak strength and overall weakening." Although the performance has declined, it still maintains a certain electromagnetic wave absorption capability.
[0091] Comparative Example 1
[0092] This embodiment uses the method of Example 1 to prepare an electromagnetic wave absorbing film, the difference being that the amount of short-cut carbon fiber added in step 5 is 1.23g.
[0093] like Figure 4 As shown, the electromagnetic wave absorbing film prepared has a performance level of "just meeting the standard": the reflection loss of all thicknesses barely exceeds -10dB (the deepest is -13.5dB), and the maximum effective absorption bandwidth (EAB) is 3.5GHz.
[0094] As can be seen from Examples 1, 2, and Comparative Example 1, the variation in the content of chopped carbon fibers can regulate the electromagnetic wave absorption performance of the prepared electromagnetic wave absorbing film. A chopped carbon fiber content of 10–20% of the total mass of paraformaldehyde and melamine (as shown in Examples 1 and 2) is optimal; however, as the amount of chopped carbon fibers added decreases, the performance also decreases. The optimal performance is achieved with a chopped carbon fiber content of 10% (Example 1), where, at a thickness of 2.0 mm, the minimum reflection loss reaches −35.4 dB, corresponding to an effective absorption bandwidth of 4.1 GHz (10.4–14.5 GHz) at a −10 dB depth. Further thickness tuning allows for stable breakthroughs of −20 dB at each thickness range of 1.5–3.0 mm, jointly covering a continuous frequency band of approximately 11.6 GHz from 6.4 to 18.0 GHz. In contrast, when the proportion of short-cut carbon fibers is 20%, the prepared electromagnetic wave absorbing film only exhibits a sharp resonance peak of −54.8 dB near 1.5 mm and 17.8 GHz, but the response bandwidth is only 2.9 GHz, which is typical of narrowband strong absorption. The maximum EAB of a single thickness is 3.7 GHz, and the combined coverage narrows to 7.0–18.0 GHz. Overall, the 10% proportion achieves the best performance in terms of strong absorption (−35.4 dB), wide bandwidth (4.1 GHz), and thickness robustness (strong absorption at multiple thicknesses), demonstrating a balanced advantage of "thin thickness, strong absorption, and wide frequency band," making it a more valuable absorbing material for engineering applications.
[0095] Example 3
[0096] The electromagnetic wave absorbing thin film of the present invention is prepared by the following method:
[0097] Step 1: Add 10g of paraformaldehyde and 100g of deionized water to a beaker and heat to 80°C while stirring continuously.
[0098] Step 2: Add 2g of melamine to the solution and continue stirring at 80℃ until completely dissolved.
[0099] Step 3: Slowly add ammonia water dropwise until the solution changes from cloudy to transparent to obtain a prepolymerized solution.
[0100] Step 4: Cool the solution to room temperature and freeze-dry for 3 days to obtain a white, fluffy melamine-formaldehyde resin powder.
[0101] Step 5: Mix white fluffy melamine-formaldehyde resin powder with 1.2g of chopped carbon fiber, add 6.6mL of deionized water, continue stirring until uniformly dispersed, and then dry at 50℃ to obtain a solid mixture.
[0102] Step 6: Pyrolyze the solid mixture in an inert gas N2 for 300 minutes at a pyrolysis temperature of 700℃.
[0103] Step 7: After pyrolysis, the aerogel is ground to obtain carbon-based microwave absorbing filler.
[0104] Step 8: Dissolve 26.4g of styrene-butadiene-styrene in 264mL of cyclohexane and heat at 100℃ for 1h to obtain a thermoplastic elastomer solution.
[0105] Step 9: Add 13.2g of carbon-based microwave absorbing filler to the thermoplastic elastomer solution, and disperse the filler evenly in the thermoplastic elastomer solution by ultrasonic dispersion to form a stable suspension.
[0106] Step 10: Pour the stable suspension into a mold and form a thin film separately using the solution casting method. After drying, an electromagnetic wave absorbing film with rapid repair capability is obtained.
[0107] like Figure 5 As shown, the electromagnetic wave absorbing film prepared in this embodiment can maintain its electromagnetic wave absorption performance. Compared with Example 1, the absorption performance decreases slightly as the proportion of melamine added decreases, but the difference is small.
[0108] Example 4
[0109] The electromagnetic wave absorbing thin film of the present invention is prepared by the following method:
[0110] Step 1: Add 10g of paraformaldehyde and 100g of deionized water to a beaker and heat to 80°C while stirring continuously.
[0111] Step 2: Add 2g of melamine to the solution and continue stirring at 80℃ until completely dissolved.
[0112] Step 3: Slowly add ammonia water dropwise until the solution changes from cloudy to transparent to obtain a prepolymerized solution.
[0113] Step 4: Cool the solution to room temperature and freeze-dry for 3 days to obtain a white, fluffy melamine-formaldehyde resin powder.
[0114] Step 5: Mix white fluffy melamine-formaldehyde resin powder with 1.2g of chopped carbon fiber, add 6.6mL of deionized water, continue stirring until uniformly dispersed, and then dry at 50℃ to obtain a solid mixture.
[0115] Step 6: Pyrolyze the solid mixture in an inert gas N2 for 360 minutes at a pyrolysis temperature of 600℃.
[0116] Step 7: After pyrolysis, the aerogel is ground to obtain carbon-based microwave absorbing filler.
[0117] Step 8: Dissolve 26.4g of styrene-butadiene-styrene in 264mL of cyclohexane and heat at 100℃ for 1h to obtain a thermoplastic elastomer solution.
[0118] Step 9: Add 13.2g of carbon-based microwave absorbing filler to the thermoplastic elastomer solution, and disperse the filler evenly in the thermoplastic elastomer solution by ultrasonic dispersion to form a stable suspension.
[0119] Step 10: Pour the stable suspension into a mold and form a thin film separately using the solution casting method. After drying, an electromagnetic wave absorbing film with rapid repair capability is obtained.
[0120] like Figure 6 As shown, the electromagnetic wave absorbing film prepared in this embodiment can maintain its electromagnetic wave absorption performance. Compared with Example 3, the absorption performance decreases slightly with the decrease of pyrolysis temperature, but the difference is small.
[0121] Example 5
[0122] The electromagnetic wave absorbing thin film of the present invention is prepared by the following method:
[0123] Step 1: Add 10g of paraformaldehyde and 100g of deionized water to a beaker and heat to 80°C while stirring continuously.
[0124] Step 2: Add 2g of melamine to the solution and continue stirring at 80℃ until completely dissolved.
[0125] Step 3: Slowly add ammonia water dropwise until the solution changes from cloudy to transparent to obtain a prepolymerized solution.
[0126] Step 4: Cool the solution to room temperature and freeze-dry for 3 days to obtain a white, fluffy melamine-formaldehyde resin powder.
[0127] Step 5: Mix white fluffy melamine-formaldehyde resin powder with 1.2g of chopped carbon fiber, add 6.6mL of deionized water, continue stirring until uniformly dispersed, and then dry at 50℃ to obtain a solid mixture.
[0128] Step 6: Pyrolyze the solid mixture in an inert gas N2 for 300 minutes at a pyrolysis temperature of 800℃.
[0129] Step 7: After pyrolysis, the aerogel is ground to obtain carbon-based microwave absorbing filler.
[0130] Step 8: Dissolve 26.4g of styrene-butadiene-styrene in 264mL of cyclohexane and heat at 100℃ for 1h to obtain a thermoplastic elastomer solution.
[0131] Step 9: Add 13.2g of carbon-based microwave absorbing filler to the thermoplastic elastomer solution, and disperse the filler evenly in the thermoplastic elastomer solution by ultrasonic dispersion to form a stable suspension.
[0132] Step 10: Pour the stable suspension into a mold and form a thin film separately using the solution casting method. After drying, an electromagnetic wave absorbing film with rapid repair capability is obtained.
[0133] like Figure 7 As shown, the electromagnetic wave absorbing film prepared in this embodiment can maintain its electromagnetic wave absorption performance. Compared with Example 4, the absorption performance also decreases slightly with the increase of pyrolysis temperature, but the difference is small.
[0134] As can be seen from Examples 3, 4 and 5, in order to obtain better electromagnetic wave absorption performance, the preferred pyrolysis temperature is 700℃.
[0135] Example 6
[0136] The electromagnetic wave absorbing thin film of the present invention is prepared by the following method:
[0137] Step 1: Add 20g of paraformaldehyde and 100g of deionized water to a beaker and heat to 100℃ while stirring continuously.
[0138] Step 2: Add 6.67g of melamine to the solution and continue stirring at 100℃ until completely dissolved.
[0139] Step 3: Slowly add ammonia water dropwise until the solution changes from cloudy to transparent to obtain a prepolymerized solution.
[0140] Step 4: Cool the solution to room temperature and freeze-dry for 2 days to obtain a white, fluffy melamine-formaldehyde resin powder.
[0141] Step 5: Mix white fluffy melamine-formaldehyde resin powder with 2.67g of chopped carbon fiber, add 15mL of deionized water, continue stirring until evenly dispersed, and then dry at 60℃ to obtain a solid mixture.
[0142] Step 6: Pyrolyze the solid mixture in an inert gas N2 for 360 minutes at a pyrolysis temperature of 600℃.
[0143] Step 7: After pyrolysis, the aerogel is ground to obtain carbon-based microwave absorbing filler.
[0144] Step 8: Dissolve 58.68g of styrene-butadiene-styrene in 586.8mL of cyclohexane and heat at 150℃ for 1h to obtain a thermoplastic elastomer solution.
[0145] Step 9: Add 29.34g of carbon-based microwave absorbing filler to the thermoplastic elastomer solution, and disperse the filler evenly in the thermoplastic elastomer solution by ultrasonic dispersion to form a stable suspension.
[0146] Step 10: Pour the stable suspension into a mold and form a thin film separately using the solution casting method. After drying, an electromagnetic wave absorbing film with rapid repair capability is obtained.
[0147] like Figure 8 As shown, the electromagnetic wave absorbing film prepared in this embodiment can maintain its electromagnetic wave absorption performance. Compared with Example 3, the absorption performance decreases slightly with the increase of the proportion of melamine added, but the difference is small.
[0148] As can be seen from Examples 1, 3, and 6, in order to obtain better electromagnetic wave absorption performance, the preferred mass ratio of paraformaldehyde to melamine is 3.9:1.
[0149] Example 7
[0150] The electromagnetic wave absorbing thin film of the present invention is prepared by the following method:
[0151] Step 1: Add 20g of paraformaldehyde and 100g of deionized water to a beaker and heat to 100℃ while stirring continuously.
[0152] Step 2: Add 6.67g of melamine to the solution and continue stirring at 100℃ until completely dissolved.
[0153] Step 3: Slowly add ammonia water dropwise until the solution changes from cloudy to transparent to obtain a prepolymerized solution.
[0154] Step 4: Cool the solution to room temperature and freeze-dry for 2 days to obtain a white, fluffy melamine-formaldehyde resin powder.
[0155] Step 5: Mix white fluffy melamine-formaldehyde resin powder with 2.67g of chopped carbon fiber, add 15mL of deionized water, continue stirring until evenly dispersed, and then dry at 60℃ to obtain a solid mixture.
[0156] Step 6: Pyrolyze the solid mixture in an inert gas N2 for 300 minutes at a pyrolysis temperature of 800℃.
[0157] Step 7: After pyrolysis, the aerogel is ground to obtain carbon-based microwave absorbing filler.
[0158] Step 8: Dissolve 58.68g of styrene-butadiene-styrene in 586.8mL of cyclohexane and heat at 150℃ for 1h to obtain a thermoplastic elastomer solution.
[0159] Step 9: Add 29.34g of carbon-based microwave absorbing filler to the thermoplastic elastomer solution, and disperse the filler evenly in the thermoplastic elastomer solution by ultrasonic dispersion to form a stable suspension.
[0160] Step 10: Pour the stable suspension into a mold and form a thin film separately using the solution casting method. After drying, an electromagnetic wave absorbing film with rapid repair capability is obtained.
[0161] like Figure 9 As shown, the electromagnetic wave absorbing film prepared in this embodiment can maintain its electromagnetic wave absorption performance.
[0162] Example 8
[0163] This embodiment demonstrates a repair experiment on an electromagnetic wave absorbing thin film. A film with a thickness of approximately 1.5 mm and dimensions of approximately 50 × 10 mm was prepared using the method described in Example 1. 2 A thin film was cut to simulate a damaged state. The following method was used for film repair:
[0164] 1. Remove surface contaminants by washing with water, and dry with 50℃ hot air for 20 minutes (extend the drying time if the temperature is low, such as drying with 40℃ hot air for 30 minutes).
[0165] 2. Apply cyclohexane to the damaged area 10 times, with a 30-second interval between each application, to induce swelling of the film.
[0166] 3. After swelling, attach the damaged area along the incision, apply 50N of pressure and hold for 30 seconds to promote bonding of the swollen area (extend the holding time if the pressure is lower, e.g., hold 10N of pressure for 300 seconds). The splicing and bonding method can be an overlapping method (e.g., ...). Figure 10 (as shown) and docking method (such as) Figure 11 (As shown).
[0167] 4. After the solvent has completely evaporated, remove the pressure, stretch the damaged area, and if there is no breakage, splicing and bonding will achieve the repair of the broken film.
[0168] The interface of the film repaired by the overlapping method was observed using scanning electron microscopy, such as... Figure 12As shown in the figure, A represents the first film layer, B represents the second film layer, and C represents the repaired surface after swelling. The figure demonstrates that the repaired film exhibits a continuous and compact interfacial structure with no obvious pores or delamination.
[0169] The mechanical properties of the thin film before and after repair were tested, such as... Figure 13 As shown, before repair (a), the maximum strain of the film reached 3.72 MPa, and the maximum stress reached 1.35 MPa, exhibiting high flexibility and strong tensile strength. After repair (b), a weak point formed at the fracture site, and the maximum strain under tension reached 2.3 MPa, and the maximum stress reached 1.03 MPa. The strain decreased by 38.2%, but still remained above 2.0, ensuring the elasticity after repair. The stress decreased by 23.7%, which was less than the decrease in strain performance, thanks to the sufficiently tight interconnection of the films. More importantly, the repair process did not change the composition before and after, and the electromagnetic wave absorption performance was not affected. Therefore, the performance of the repaired film decreased slightly, but it still maintained its flexibility and wave absorption properties.
[0170] Comparative Example 2
[0171] This embodiment uses the following method to prepare an electromagnetic wave absorbing thin film:
[0172] 1. Styrene-butadiene-styrene (3000 mg) was dissolved in cyclohexane (60 mL), and the mixture was heated at 120 °C for 2 hours to promote dissolution and obtain a cyclohexane solution of styrene-butadiene-styrene.
[0173] 2. Add a mixture of carbonyl iron powder (3600mg) and carbon nanotubes (75mg), and stir mechanically (1200rpm) for 2 hours to ensure uniform dispersion of the powder filler.
[0174] 3. Place the suspension in a mold and dry at 30°C for 12 hours to remove the solvent and obtain a thin film.
[0175] Repair tests were conducted on the prepared electromagnetic wave absorbing thin film, which was approximately 1.5 mm thick and 50 × 10 mm in size. 2 A thin film was cut to simulate a damaged state. The following method was used for film repair:
[0176] 1. Remove surface contaminants by washing with water, and dry with 50℃ hot air for 20 minutes (extend the drying time if the temperature is low, such as drying with 40℃ hot air for 30 minutes).
[0177] 2. Apply cyclohexane to the damaged area 10 times, with a 30-second interval between each application, to induce swelling of the film.
[0178] 3. After swelling, attach the damaged area along the incision, apply 50N of pressure and hold for 30 seconds to promote the connection of the swollen area (if the pressure is low, extend the holding time, such as holding 10N of pressure for 300 seconds). The splicing and bonding method can be the overlapping method.
[0179] 4. After the solvent has completely evaporated, remove the pressure, stretch the damaged area, and if there is no breakage, splicing and bonding will achieve the repair of the broken film.
[0180] Simultaneously, performance tests were conducted on electromagnetic wave absorbing films of different thicknesses prepared according to this comparative ratio, such as... Figure 14 As shown, this sample exhibits superior absorption performance, with a reflection loss of -39.2 dB. The five thicknesses collectively cover approximately 13.6 GHz (4.4–18.0 GHz), spanning the entire C / X / Ku band. However, the electromagnetic wave absorbing filler (i.e., a mixture of carbonyl iron powder and carbon nanotubes) in this electromagnetic wave absorbing film constitutes 122.5% of the thermoplastic elastomer's mass, significantly higher than the 50% addition amount in Example 1.
[0181] Comparative Example 3
[0182] This embodiment uses the following method to prepare an electromagnetic wave absorbing thin film:
[0183] 1. Styrene-butadiene-styrene (3000 mg) was dissolved in cyclohexane (60 mL), and the mixture was heated at 120 °C for 2 hours to promote dissolution and obtain a cyclohexane solution of styrene-butadiene-styrene.
[0184] 2. Add a mixture of carbonyl iron powder (1200mg) and carbon nanotubes (300mg), and stir mechanically (1200rpm) for 2 hours to ensure uniform dispersion of the powder filler.
[0185] 3. Place the suspension in a mold and dry at 30°C for 12 hours to remove the solvent and obtain a thin film.
[0186] Repair tests were conducted on the prepared electromagnetic wave absorbing thin film, which was approximately 1.5 mm thick and 50 × 10 mm in size. 2 A thin film was cut to simulate a damaged state. The following method was used for film repair:
[0187] 1. Remove surface contaminants by washing with water, and dry with 50℃ hot air for 20 minutes (extend the drying time if the temperature is low, such as drying with 40℃ hot air for 30 minutes).
[0188] 2. Apply cyclohexane to the damaged area 10 times, with a 30-second interval between each application, to induce swelling of the film.
[0189] 3. After swelling, attach the damaged areas along the incision, apply 30N of pressure and hold for 30 seconds to promote the connection of the swollen areas (extend the holding time if the pressure is low, such as holding 10N of pressure for 300 seconds). The splicing and bonding method can be the overlapping method.
[0190] 4. After the solvent has completely evaporated, remove the pressure, stretch the damaged area, and if there is no breakage, splicing and bonding will achieve the repair of the broken film.
[0191] Meanwhile, performance tests were conducted on electromagnetic wave absorbing films of different thicknesses prepared according to this comparative example. The proportion of electromagnetic wave absorbing filler in the electromagnetic wave absorbing film of this comparative example was similar to that in Example 1, but the performance of this sample was significantly weaker than that of Comparative Example 2. The strongest absorption was -22.9 dB, far lower than the electromagnetic wave absorbing film prepared in Example 1. At 2.5 mm / 3.0 mm, it barely reached -10 dB, and the absorption bandwidth narrowed to about 1 GHz. Figure 15 As shown, the electromagnetic wave absorbing thin film prepared in this comparative example has weak overall performance and lacks broadband and thickness tuning capabilities.
[0192] As can be seen from Examples 1, 2, and 3, when the carbon-based absorbing filler is prepared using a process that incorporates magnetic materials (Comparative Examples 2 and 3), the corresponding electromagnetic wave absorbing film requires a relatively high mass percentage of absorbing filler to ensure electromagnetic wave absorption performance, thus affecting repairability. On the other hand, reducing the amount of absorbing filler to ensure rapid repairability of the film compromises electromagnetic wave absorption performance. The electromagnetic wave absorbing film prepared by incorporating carbon-based absorbing materials in this invention can simultaneously guarantee both electromagnetic wave absorption performance and repairability.
[0193] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. An electromagnetic wave absorbing thin film, characterized in that, The electromagnetic wave absorbing film is obtained by uniformly dispersing carbon-based absorbing filler in a thermoplastic elastomer solution to obtain a suspension, and then coating the suspension onto the surface of an object to form a coating or film, which is then dried. The thermoplastic elastomer solution is prepared by heating and dissolving the thermoplastic elastomer in an organic solvent; the amount of thermoplastic elastomer added is 1.8-2.2 times the total amount of paraformaldehyde, melamine, and chopped carbon fibers; the thermoplastic elastomer is a polyurethane-based thermoplastic elastomer, a styrene-based thermoplastic elastomer, or a thermoplastic styrene-butadiene rubber polymer; the organic solvent is selected from dimethylformamide, cyclohexane, or acetone. The carbon-based microwave absorbing filler is prepared by the following method: Step 1: Mix paraformaldehyde and deionized water at a mass ratio of 1:5 to 1:10, and stir continuously at 80℃ to 100℃ for 1 to 2 hours to obtain a paraformaldehyde dispersion. Step 2: Add melamine to the paraformaldehyde dispersion from Step 1, and continue stirring at 80°C to 100°C until the melamine is completely dissolved; the mass ratio of paraformaldehyde to melamine is 5:1 to 3:
1. Step 3: Add ammonia water dropwise to the dispersion in which melamine was dissolved in Step 2. The dispersion gradually changes from turbid to transparent to obtain a prepolymer solution. Step 4: After cooling the prepolymer solution obtained in Step 3 to room temperature, freeze-dry it under vacuum for 2-3 days to obtain a white, fluffy melamine-formaldehyde resin powder. Step 5: Take the melamine-formaldehyde resin powder and chopped carbon fibers from Step 4, mix them, add deionized water and stir evenly, then dry at 50-60°C to obtain a solid mixture; the amount of chopped carbon fibers added accounts for 5%-25% of the total mass of paraformaldehyde and melamine, and the amount of deionized water added accounts for 40%-60% of the total mass of paraformaldehyde, melamine and chopped carbon fibers. Step 6: Pyrolyze the solid mixture from Step 5 in an inert gas for 300 to 360 minutes to prepare an aerogel, with the pyrolysis temperature controlled at 600℃ to 800℃. Step 7: Grind the aerogel obtained in step 6 to obtain the carbon-based microwave absorbing filler.
2. The electromagnetic wave absorbing thin film according to claim 1, characterized in that, The mass ratio of paraformaldehyde to melamine is 3.9:1; the amount of short-cut carbon fiber added is 10% of the total mass of paraformaldehyde and melamine.
3. The electromagnetic wave absorbing thin film according to claim 2, characterized in that, In step 6, the pyrolysis temperature is 700℃ and the pyrolysis time is 300 minutes.
4. The electromagnetic wave absorbing thin film according to claim 1, characterized in that, The thickness of the electromagnetic wave absorbing film is 1.5 mm to 3 mm.
5. The electromagnetic wave absorbing thin film according to claim 4, characterized in that, The electromagnetic wave absorbing thin film is prepared by the following steps: Step 1: Dissolve the thermoplastic elastomer in an organic solvent and heat at 80℃~150℃ for 0.5h~4h to obtain the thermoplastic elastomer solution; the concentration of thermoplastic elastomer in the thermoplastic elastomer solution is 10mg / mL~100mg / mL; Step 2: Add the carbon-based microwave absorbing filler to the thermoplastic elastomer solution, and disperse the carbon-based microwave absorbing filler evenly in the thermoplastic elastomer solution by mechanical stirring or ultrasonic dispersion to form a stable suspension; Step 3: Apply the stable suspension to the surface of the object to form a coating or a thin film, and obtain the electromagnetic wave absorbing film after drying.
6. A rapid repair method for the electromagnetic wave absorbing thin film according to any one of claims 1 to 5, characterized in that, Includes the following steps: Step 1: When the electromagnetic wave absorbing film is damaged, remove surface contaminants by washing with water and then dry with hot air. Step 2: Apply an organic solvent to the damaged area of the electromagnetic wave absorbing film or soak it in an organic solvent to induce swelling in the damaged area of the substrate; the organic solvent is the same organic solvent used in the preparation of the electromagnetic wave absorbing film, and the organic solvent is dimethylformamide, cyclohexane or acetone. Step 3: Join the swollen areas together and apply pressure to promote bonding of the swollen areas; Step 4: After the solvent in the swollen area has completely evaporated, remove the pressure and stretch the repaired damaged area. If there is no breakage, the repair is complete.
7. The rapid repair method for the electromagnetic wave absorbing thin film according to claim 6, characterized in that, In step 2, when applying organic solvent to the damaged area, the number of applications is 3 to 10, with an interval of 10 to 30 seconds between each application; when immersing the damaged area in organic solvent, the immersion time is 30 to 300 seconds.
8. The rapid repair method for the electromagnetic wave absorbing thin film according to claim 7, characterized in that, In step 3, the splicing and bonding adopts an overlapping method or a butt joint method, wherein the overlap width is 5mm~10mm; the applied pressure is 10~50N, and the pressure application time is 30~300 seconds.
Citation Information
Patent Citations
Light flexible multi-band electromagnetic wave absorbing material based on sub-wavelength material and preparation method of light flexible multi-band electromagnetic wave absorbing material
CN112234364A
Preparation method of self-repairing electromagnetic composite material
CN116376268A